CHANGES OF CHEMICAL COMPOSITION OF ROCKS IN THE PROCESS OF CONTACT-METASOMATIC GRANITIZATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Contact-metasomatic granitization is a complicated process and is expressed by formation of contact homfels (izochemical metamorphism), afterwards iron-magnezial (bazification) and silica-alkaline (proper granitization) metasomatism. In the article the chemical composition of contact homfels, bazificated and granitizied rocks and also intrusive aplitic granites is stated. On the diagrams it's properly defined the behavior of elements of granitizied series of rocks - alkaline elements, aluminum and elements of dark minerals (calcium, magnesium, iron) during the process of granitization. Granitization is accompanied by a huge entrance (K, Si) and exit (Ca, Mg, Fe) of substance, which approves the metasomatic character of the process.
Keywords: contact-metasomatic granitization; izochemical metamorphism; contact homfels; iron-magnezial; silica-alkaline